2017
DOI: 10.1016/j.ypmed.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Where Latin Americans are physically active, and why does it matter? Findings from the IPEN-adult study in Bogota, Colombia; Cuernavaca, Mexico; and Curitiba, Brazil

Abstract: Latin America (LA) has a unique structural, political, cultural and social environment. This study aimed to identify the places where Latin American adults are physically active; and to determine the association of using public- and restricted-access places with physical activity (PA). We used data from the International PA Environment Network study in Bogota, Colombia (n=1000, accelerometry=249); Cuernavaca, Mexico (n=677, accelerometry=652); and Curitiba, Brazil (n=697, accelerometry=331) (2010-2011). Walkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 52 publications
(49 reference statements)
7
76
0
9
Order By: Relevance
“…Several land-use and transportation factors are known to be associated with active commuting [9,37,39,40]. Consistent with other international studies from both high-income countries and LMICs, the strongest correlate of active commuting and use of public transit was land use mix [24,[41][42][43].…”
Section: Comparison With Existing Literaturesupporting
confidence: 71%
See 2 more Smart Citations
“…Several land-use and transportation factors are known to be associated with active commuting [9,37,39,40]. Consistent with other international studies from both high-income countries and LMICs, the strongest correlate of active commuting and use of public transit was land use mix [24,[41][42][43].…”
Section: Comparison With Existing Literaturesupporting
confidence: 71%
“…Achieving increased active commuting requires coordinated work among various stakeholders, but the benefits are numerous, and go beyond physical inactivity and sedentary lifestyles, including positive impacts on traffic congestion, air pollution, and carbon emissions [66,67]. However, the present study adds to other evidence from LMICs [35,37,48] that car ownership appears to negate any effect of walkable neighborhood design on active commuting. Thus, special efforts may be needed to encourage car owners in LMICs to walk for transport, in addition to activity supportive built environments.…”
Section: Conclusion and Next Stepsmentioning
confidence: 64%
See 1 more Smart Citation
“…In this sense, the access to locations such as parks, plazas and bicycle routes becomes important for the development of active healthy lifestyles in the population [2][3][4][5] . Aspects such as the availability of areas for walking, green areas and access to recreational facilities as well as the aesthetics of the surroundings are positively associated with physical activity 1,2,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that living in areas of low socioeconomic level is inversely associate to physical activity, which could be explained by lack of adequate spaces for practice [13][14][15] . This is important, once in Colombia (Bogotá) it was found that 55% of the population uses parks and plazas for physical activity and, moreover, that the use of these spaces can increase in 310% the likelihood of reaching the recommendations of physical activity for health, in leisure time 5 .…”
Section: Introductionmentioning
confidence: 99%